Pengaruh Profitabilitas, Solvabilitas, Kompleksitas Operasi, Reputasi Kap, Umur Perusahaan Terhadap Audit Report Lag(Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015) - Tri Isnaini, Ridwan; , Dr. Noer Sasongko, SE, M.Si, Ak (2017)
This research was aimed to examine the effect of profitability, solvability, complexity of operation, KAP reputation, and company age toward audit report lag on companies listed in the Indonesia stock exchange in the period of 2013 - 2015. The data used in this research was secondary data obtained from the annual report and auditors' report of manufacturing companies listed in The Indonesia Stock Exchange in 2013-2015. The sampling technique in this research was done by using purposive sampling technique. Samples that met the criteria were 29 companies. The techniques of analysis applied to observe the effect of the independent variables toward the dependent variable in this research was performed by multiple linear regression analysis. Results of analysis showed that simultaneously ROA (Profitability), and KAP (Public Accounting Firm) has effect on ARL (Audit Report Lag), whereas SOL (Solvability), KO (Complexity of Operation), and UMR (Company Age) has no effect on ARL (Audit Report Lag). Partially ROA (Profitability), and KAP (Public Accounting Firm) has effect on ARL (Audit Report Lag), whereas SOL (Solvability), KO (Complexity of Operation), and UMR (Company Age) has no effect on ARL (Audit Report Lag).